2021
DOI: 10.7189/jogh.11.04023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mobile health on emergency care in low- and middle-income countries: A systematic review and narrative synthesis

Abstract: Background In resource-constrained settings, mobile health (mHealth) has varied applications. While there is strong evidence for its use in chronic disease management, the applications of mHealth for management of acute illness in low- and middle-income countries (LMICs) are not as well described. This review systematically explores current available evidence on the effectiveness of mHealth interventions at improving health outcomes in emergency care settings in LMICs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…The GEMLR platform has been used to evaluate narrower topics in systematic reviews published elsewhere. [19][20][21][22] Recognizing that important clinical guidance is at times also found in non-peer-reviewed "gray" literature produced by various international organizations, 23 we also supplement the review of published literature with a manual search and review of new guidance found on the websites of several key organizations, including academic think thanks and prominent humanitarian governmental and nongovernmental organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The GEMLR platform has been used to evaluate narrower topics in systematic reviews published elsewhere. [19][20][21][22] Recognizing that important clinical guidance is at times also found in non-peer-reviewed "gray" literature produced by various international organizations, 23 we also supplement the review of published literature with a manual search and review of new guidance found on the websites of several key organizations, including academic think thanks and prominent humanitarian governmental and nongovernmental organizations.…”
Section: Introductionmentioning
confidence: 99%
“…A subgroup of the GEMLR team began publishing a systematic review to further highlight and synthesize areas of GEM research that have broad clinical relevance 20–23 . Its most recent publications highlighted interventions for patients with severe acute respiratory infections (including 34 of 58 articles focusing on COVID‐19) in low‐ and middle‐income countries (LMICs) 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Mobile revolution applied to healthcare is a promising candidate to leverage out-of-office blood pressure monitoring as numerous systematic reviews and meta-analyses have enforced the effectiveness of mobile health to improved medical adherence by lowering both mortality and morbidity [8]. Hence, bringing to the populations a mobile application allowing them to measure accurately their blood pressure at any time would be an important step in the global health prevention strategy.…”
Section: Introductionmentioning
confidence: 99%